Access Control and File Distribution Management for Electronic Diploma and Transcript using Ethereum Smart Contract and InterPlanetary File System - Muhammad Danil Muis; Muhammad Rifki Fauzan; Parman Sukarno; Aulia Arif Wardana (Faculty of Computer Science Universitas Indonesia, 2021)
This reserach build access control and file distribution management system for electronic diploma and transcript using ethereum smart contract and InterPlanetary File System (IPFS). The falsification of diplomas/transcripts is one of the problems in education. In Indonesia, falsification of diplomas/transcripts is a form of criminal act of falsifying letters. In addition, diplomas/transcripts that have not been digitalized make them easily damaged, lost, and difficult to manage. Therefore, this research developed digital diploma/transcript as digital twin from the hardcopy of diploma/tramscript. This research used IPFS to store data in a distributed system and Smart Contracts Blockchain to store and protect the digital diploma/transcript. The system also comes with access control to create and give approval for diplomas or transcripts to be published and saved into the system. Access control settings will be saved using the blockchain. This research using Quality of Service test method for measurethroughput, packet loss, and delay. Beside that, tis research also analysis the usage of Central Processing Unit and Random Access Memory from the system. Based on the test that has been done, the fake diploma/transcript detection system can be run properly by using 1 node to 5 nodes. The best throughput value during the process of making and validating the diploma/transcript is to use 1 node. The value of packet loss in the process of making and validating the certificate/transcript has a very good category. The value of delay in the process of making and validating the diploma/transcript has a very good category.